A CASE OF RIGHT VENTRICLE IDIOPATHIC IMPAIRMENT, DATA OF A CARDIOLOGY UNIT - M. Y. Grigoryev; O. M. Yedigarova; S. M. Svatenko (Российский кардиологический журнал)
A case of right ventricle idiopathic impairment, data of a cardiology unit.